Factors Associated with Not Using a Condom at Last Sex Among Sexually Active US Navy and Marine Corps Personnel Across a Shipboard Deployment. (4th October 2017) - Harbertson, Judith; De Vera, Kimberly; Scott, Paul; Shaffer, Richard; Michael, Nelson; Hale, Braden
Abstract: Background: Condom use is highly effective in preventing sexually transmitted infections (STIs); however, data on this are limited among US military personnel who may be at a higher risk for STI acquisition across a deployment cycle. This study examined factors associated with no condom use at last sex at three time points, pre- (T1), during (T2), and post-deployment (T3), across a US military shipboard deployment cycle. Methods: Data were collected among active duty US Navy and Marine Corps personnel assigned to 11 deploying ships using an anonymous, voluntary, self-completed survey, including demographics, condom use at last sex, sexual risk behavior, STI diagnosis, alcohol misuse (Alcohol Use Disorders Identification Test–Consumption), and drug use with sex. Descriptive and generalized regression model analyses were conducted to determine the effects of main exposures after adjusting for demographic characteristics, with statistical significance defined as P < 0.05. When longitudinal data were included, generalized estimating equations were used. Models included their interaction with time. Results: Among participants, n  = 1, 900 (T1), n  = 549 (T2), and n  = 1, 168 (T3) reported age and sex, were sexually active, and included in the analysis. The proportion of individuals who used a condom at last sex was significantly higher during T2 (53%, P < 0.0001) than T1 (27%) and T3 (28%), with an STI prevalence of 1% (T1), 7% (T2), and 2% (T3). In adjusted models, participants not using a condom at last sex were significantly more likely to report an STI diagnosis (OR 2.26, 95% CI 1.19–4.28), screen positive for hazardous alcohol use (OR 1.44, 95% CI 1.21–1.71), and use drugs to enhance sex (OR 1.37, 95% CI 1.06–1.77), but less likely to engage in transactional sex (OR 0.69, 95% CI 0.50–0.94). Associations between condom use and main exposures did not differ significantly by time point. Conclusion: Although condom use was significantly higher during T2, STI prevalence remained high, which suggests those who do not use a condom during deployment are at a higher risk for STI acquisition than pre- or post-deployment. These data may inform interventions targeting high STI acquisition risk individuals and time periods to increase condom use. Disclosures: All authors: No reported disclosures.